Strategies to Improve Endothelial Function and its Clinical Relevance to Erectile Dysfunction - Aversa, Antonio (European urology supplements : official journal of the European Association of Urology, 2009)
Erectile dysfunction (ED) is often the manifestation of a generalized vascular disorder characterized by endothelial dysfunction. Reduced biological activity of endothelium-derived nitric oxide links human atherosclerosis to ED and underscores the role of an altered endothelium in the pathogenesis of both conditions. This review will provide an update on clinical data available on drugs promoting endothelial health and repair with regard to sexual medicine. A comprehensive evaluation of available published data in full-length papers, identified in MedLine up to February 2008, was performed. Evidence indicates that angiotensin-converting-enzyme inhibitors, sartanes, statins, vitamins (C and E), and L-arginine are all effective drugs for improving endothelial dysfunction in clinical studies; real benefits of dietary vitamin supplements and nutraceuticals are questionable. Growing evidence suggests that continued use of phosphodiesterase type 5 inhibitors as well as adjunctive testosterone replacement in deficiency syndromes may be beneficial and may synergistically improve endothelial function in selected subjects. Endothelially active drugs may serve as active treatment for both general and sexual health in men with increased cardiovascular risk. Further controlled studies are necessary to establish the real cost-effectiveness of such therapies and their impact on outcomes for patients. An altered endothelium plays a crucial role in the pathogenesis of both erectile dysfunction and atherosclerosis. Although growing evidence in selected subjects suggests a potential beneficial effect on endothelial function from chronic exposure to several drugs, including phosphodiesterase type 5 inhibitors or adjunctive testosterone, the real clinical implications remain unknown. Further controlled, long-term, multicenter studies are necessary to assess the impact of these drugs on clinical outcomes for patients.